Determining thyrotropin receptor and thyroglobulin gene transcripts in peripheral blood of thyroid carcinoma patients and healthy individuals - Makazlieva, Tanja; Vaskova, Olivija; Tripunoski, Toni; Miladinova, Daniela; Stojanoski Sinisa; Manevska, Nevena; Jakovski Z; Risteski, Sasho; Jovanovic H; Eftimov A (Springer Science and Business Media LLC, 2018)
Introduction: Thyroid carcinoma (TC) comprises a spectrum of different tumors with wide range of biological behavior and prognosis. The techniques based on the latest trends in molec- ular biology may have application in diagnosis of metastatic TC. The aim of this study was to apply and analyze mRNA expres- sion of thyrotropin receptor gene (TSHR-mRNA) and thyroglob- ulin gene (Tg-mRNA) in peripheral blood of healthy individuals and patients with differentiated TC. Then to correlate between the total received 131 I therapy dose and expression levels of two evaluated genes. Material and Methods: In the study were included 57 subjects, consisting from 40 patients with TC and 17 healthy volunteers as a control group. Total RNA was isolat- ed from peripheral blood and used for two-step reverse tran- scriptase-PCR. Real time PCR was performed with appropriate primers. Relative quantification using 2-ΔΔCt method was applied. Results: TC patients with metastatic disease or loco-regional re- lapse expressed TSHR by a 8.57-fold higher level than healthy control individuals. TC patients with biochemical relapse ex- pressed TSHR by a 14.17-fold higher level than healthy controls, while expression of Tg was 6.6 -fold higher in TC patients with metastatic disease and loco-regional relapse than healthy con- trols and 8.34 -fold higher level compared with TC patients with excellent response to treatment. Conclusion: Our preliminary study showed that TSHR gene expression might have more useful application as a biomarker compared to detection of Tg gene expression. Positive non-significant correlation between ΔCt values for both target genes and total received dose of 131 I therapy with Spearman Rank was found. Key words: Thyroid carcinoma, TSH receptor gene expression, thyroglobulin gene expression
Keywords: thyroid carcinoma; thyroglobulin gene expression; tsh receptor gene expression